Which Role for Hyperbaric Oxygen Therapy in the Treatment of Fournier's Gangrene? A Retrospective Study - Tutino, Roberta; Colli, Francesco; Rizzo, Giovanna; Bonventre, Sebastiano; Scerrino, Gregorio; Salamone, Giuseppe; Melfa, Giuseppina; Orlando, Giuseppina; Gallo, Gaetano; Santarelli, Mauro; Massani, Marco; Cocorullo, Gianfranco (Frontiers in Surgery, 2022)
Purpose: In Fournier’s gangrene, surgical debridement plus antimicrobial therapy is the mainstay of treatment but can cause a great loss of tissue. The disease needs long hospital stays and, despite all, has a high mortality rate. The aim of our study is to investigate if factors, such as hyperbaric therapy, can offer an improvement in prognosis. Methodsː We retrospectively evaluated data on 23 consecutive patients admitted for Fournier’s gangrene at the University Hospital “P. Giaccone” of Palermo from 2011 to 2018. Factors related to length of hospital stay and mortality were examined. Resultsː Mortality occurred in three patients (13.1%) and was correlated with the delay between admission and surgical operation [1.7 days (C.I. 0.9-3.5) in patients who survived vs. 6.8 days (C.I. 3.5-13.4) in patients who died (p = 0.001)]. Hospital stay was longer in patients treated with hyperbaric oxygen therapy [mean 11 (C.I. 0.50-21.89) vs. mean 25 (C.I. 18.02-31.97); p = 0.02] without an improvement in survival (p = 1.00). Conclusionː Our study proves that a delay in the treatment of patients with Fournier’s gangrene has a correlation with the mortality rate, while the use of hyperbaric oxygen therapy seems to not improve the survival rate, increasing the hospital stay instead.